Some reflections on the 60th aniversary of the continuation of the Sociološki pregled / Sociologial review (1961–2021) - Antonić, Slobodan (Sociološki pregled, 2022)
On the occasion of the journal‘s anniversary, the author discusses three issues in the field of scientific policy in Serbia: the journal‘s language and script, the issue of the publisher, and the journal‘s place and role in the scientific community. The author concludes that the mass transition of scientific journals in Serbia to English, with the abolition of Serbian versions of texts (the tradition pursued by the Sociološki pregled / Sociological Review), leads not only to stopping the development of the domestic scientific terminology, but also to the stagnation and long-term disappearance of local (national) scientific communities. Scientific communities of individual countries or languages, particularly in the humanities and social sciences, are essential for scientific research of local (national) societies, their economic, social and cultural problems and specifics. Their gradual winding down can also be considered a form of cultural neocolonialism.
Keywords: scientific community; scientific policy; scientific journals; scientific language; cultural neocolonialism